Nano-formulations composed of cell membrane-specific cellular lipid extracts derived from target cells: physicochemical characterization and in vitro evaluation using cellular models of breast carcinoma - Hanan M. Alharbi; Robert B. Campbell (SpringerOpen, 2018)
Abstract Highly selective drug targeting is an important goal in the development of cancer nanotechnologies. In an effort to improve tumor targeting a method was developed to formulate cell membrane lipid-extracted nanoliposomes (CLENs). The main ingredients were extracted directly from the membrane of cancer cells. For this study we used three different breast cancer cell lines (4 T1, BT-20, and SK-BR-3). As controls for the normal breast and cancer tissue environments we employed the normal breast fibroblast (CRL-2089) and ovarian cancer (SK-OV-3) cell lines, respectively. We evaluated physicochemical properties, efficiency of drug loading, cellular uptake, and cytotoxicity. The mean diameter and zeta potential values for the 5 different CLENs were 202 ± 38 nm and − 15 ± 3.8 mv, respectively. Doxorubicin hydrochloride (5 mol%) increased the size of 4 T1-CLENs from 158 ± 2 nm to 212 ± 59 nm, with no significant change in the negatively-charged surface potential. Percent of drug loaded ranged from 40 to 93%, varying according to the ratio of lipid extract to conventional components employed. The additional inclusion of cholesterol and DPPE-PEG5000 increased drug loading in CLENs, similar to Doxil preparations. The most promising cellular uptake and cytotoxicity profiles were observed when the lipid ingredients were derived from the eventual target cell. Given the ability of CLENs to better recognize target cells compared to nanosystems consisting of non-specific lipid extracts or conventional liposome ingredients alone, CLENs has demonstrated early promise as a nano-delivery system for cancer treatment.